Efflux Inhibitory Activity Of Selected Phyto-Compounds Against Clinical Isolates Of Multidrug-Resistant Staphylococcus Aureus - Johari, Saiful Azmi (2007)
Multidrug-resistant Staphylococcus aureus (MRSA) has been reported as one of the main cause of nosocomial infection in the world and ranks as one of the most difficult bacteria to treat in hospitalized patients. Apparently, these multidrug resistance (MDR) traits are caused by an array of MDR efflux pumps in S. aureus. In this study, a panel of identified clinical S. aureus isolates were tested for their multidrug-resistance profile, detection of efflux genes and evaluated against selected phyto-compounds. From the 26 bacterial isolates acquired from two teaching hospitals (HUKM and UMMC) and three ATCC S. aureus reference strains, 19 were confirmed as S. aureus isolates. Out of the 19 isolates, 14 were confirmed as methicillin-resistant S. aureus (MetRSA) via phenotypic and genotypic methods. Fourteen MetRSA isolates exhibit multidrug-resistance against amikacin, erythromycin, gentamicin, norfloxacin, tetracycline and trimethoprim. A methicillin-sensitive S. aureus (MetSSA) with multidrug-resistant trait was also detected. Apart from vancomycin, mupirocin seems to be the most effective antibiotic against all S. aureus isolates. Two MDR efflux genes (mdeA and norA) were detected in all isolates tested. Out of the 19 isolates, 18 harboured the mdeA gene while 16 isolates contained the norA gene. Active efflux activity in S. aureus was detected using modified minimum inhibitory concentration (MIC) assay with ethidium bromide and reserpine as the efflux substrate and efflux inhibitor respectively. From this assay, two MRSA clinical isolates and one ATCC 25923 S. aureus reference strain were selected as test strains against 37 selected phyto-compounds consisting of alkaloids, flavonoids, coumarins and essential oils. Nine compounds namely quinine, harmaline, piperine, cinnamon oil, dicumarol, eriodictyol-7,4’-dimethyl ether, 2’,4-dihydroxy-4’,5’,6’- trimethoxychalcone and naringenin-4’-methyl ether exhibited good efflux inhibitory activity as compared to reserpine. The first two are alkaloids with a methoxyl group at position C6 of an indole and quinolone skeleton, respectively. The last three are flavonoids from different sub-classes of flavanone (eriodictyol-7,4’-dimethyl and ether naringenin-4’-methyl ether) and chalcone (2’,4-dihydroxy-4’,5’,6’-trimethoxychalcone). The similarity observed amongst member of the latter group is the presence of two hydroxyl group attached to their skeletal structures.